Flexible insurance for long‐term care: A study of stated preferences. Issue 3 (25th April 2022) - Wu, Shang; Bateman, Hazel; Stevens, Ralph; Thorp, Susan
Abstract: Aging societies need efficient and flexible systems to finance care for the frail elderly. We study pre‐retirees' demand for flexible insurance that can finance informal long‐term care by paying income in poor health states instead of reimbursing formal care costs. We collect and analyze stated preferences for this long‐term care income product, and preferences for informal care. When asked to allocate wealth to a life annuity, a liquid investment and flexible long‐term care insurance, around 75% of our sample of 1008 pre‐retirees choose some long‐term care cover. Study participants treat long‐term care income insurance as a complement to informal care from their families. Females who expect to rely exclusively on extensive care from family members prefer more cover than similar males. We also find that if long‐term care income insurance were available, some healthier seniors would purchase additional longevity insurance, using liquid funds otherwise set aside to self‐insure long‐term care risk.